Teachers’ Perception Towards Vocational Education Status, Standing and Challenges - Rashmi,; Singh, Abhishek Kumar (JOURNAL OF INDIAN EDUCATION, 2021)
Vocational Education is the core of any educational system in the world. The present study investigates the perception of vocational education teachers towards vocational education. This study was conducted by adopting the survey research method. A total of 250 vocational education teachers working in Government and CBSE mode were surveyed randomly with the help of a self-made questionnaire. Statistical analysis involved percentages and chi-square. Results indicated that most vocational education teachers perceive that the current status of vocational education in India is satisfactory. Yet, there is a lack of coordination among the government and different regulatory bodies. The findings contribute to the discussion and reform in the quality of vocational education in the country, specifically to increase the number of students opting for vocational education and bridging the gap between theory and practical.